2011
DOI: 10.1590/s0100-204x2011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Tannin-tolerant bacteria from crossbred Holstein x Zebu cows

Abstract: -The objective of this work was to isolate and characterize tannin-tolerant ruminal bacteria from crossbred Holstein x Zebu cows fed a chopped mixture of elephant grass (Pennisetum purpureum), young stems of "angico-vermelho" (Parapiptadenia rigida), and banana tree (Musa sp.) leaves. A total of 117 bacteria strains were isolated from enrichment cultures of rumen microflora in medium containing tannin extracts. Of these, 11 isolates were able to tolerate up to 3 g L -1 of tannins. Classical characterization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Therefore, this study was planned to investigate the chemical composition, in vitro gas production (IVGP) and fermentation parameters of Q. infectoria and Q. libani oak leaf following treatment with Klebsiella pneumoniae , a native tannase producing bacterium. The K. pneumoniae used in the present study was isolated from farm soil and this is consistent with other studies that isolated several bacterial strains with phenolic degrading potential from different sources (Arcuri et al ; Pepi et al ; Mosleh et al ).…”
Section: Introductionsupporting
confidence: 91%
“…Therefore, this study was planned to investigate the chemical composition, in vitro gas production (IVGP) and fermentation parameters of Q. infectoria and Q. libani oak leaf following treatment with Klebsiella pneumoniae , a native tannase producing bacterium. The K. pneumoniae used in the present study was isolated from farm soil and this is consistent with other studies that isolated several bacterial strains with phenolic degrading potential from different sources (Arcuri et al ; Pepi et al ; Mosleh et al ).…”
Section: Introductionsupporting
confidence: 91%
“…This indicates that there are variations in some rumen fermentation profile variables in certain tannin level categories between the in vitro and in vivo rumen studies. The study by Arcuri et al [53] found that the B. fibrisolvens and Streptococcus bovis strains isolated from Holstein  Zebu cattle resisted the biological effect of CT Mimosa artemisia extract at low levels (2-3 g L À1 ). The effect of eliminating the rumen methanogen population using tannin-sourced feeds has a direct impact on reducing the overall level of ruminant methane production.…”
Section: Discussionmentioning
confidence: 99%